2000
DOI: 10.1021/bi001528j
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Porphyrins Promote the Formation of i-Motif DNA and Bind Peripherally by a Nonintercalative Mechanism

Abstract: Telomeric C-rich strands can form a noncanonical intercalated DNA structure known as an i-motif. We have studied the interactions of the cationic porphyrin 5,10,15,20-tetra-(N-methyl-4-pyridyl)porphine (TMPyP4) with the i-motif forms of several oligonucleotides containing telomeric sequences. TMPyP4 was found to promote the formation of the i-motif DNA structure. On the basis of (1)H NMR studies, we have created a model of the i-motif-TMPyP4 complex that is consistent with all the available experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 47 publications
6
81
2
Order By: Relevance
“…Several small molecules have been shown to efficiently inhibit telomerase activity through the stabilization of G-quadruplex DNA (4, 5). Only two molecules that can stabilize both G-quadruplex and i-motif DNA have been identified (11,12). To our knowledge, a ligand that can selectively stabilize i-motif DNA but not G-quadruplex DNA has not been reported.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Several small molecules have been shown to efficiently inhibit telomerase activity through the stabilization of G-quadruplex DNA (4, 5). Only two molecules that can stabilize both G-quadruplex and i-motif DNA have been identified (11,12). To our knowledge, a ligand that can selectively stabilize i-motif DNA but not G-quadruplex DNA has not been reported.…”
mentioning
confidence: 97%
“…The helix twists in a right-handed manner, and the distance between nearest base pairs is only 3.1 Å. In contrast with the G-rich quadruplex, little is known about the interaction of small ligands with this structure (2,11,12). Only two molecules, a porphyrin derivative and an acridine dimer, have been reported to stabilize both G-quadruplex and i-motif DNA via a nonintercalative mechanism (11,12).…”
mentioning
confidence: 99%
“…We have also recently demonstrated that G-quadruplex-interactive compounds such as TMPyP4 can also facilitate the formation of i-motif DNA and bind to the resulting structure by a nonintercalative mechanism (34). This provides an additional mechanism for intervention with small molecules in the conversion of c-myc NHE between duplex and alternative secondary structures.…”
mentioning
confidence: 98%
“…Small molecules that stabilize G-quadruplexes are effective as telomerase inhibitors, and several series of compounds have been identified using techniques such as temperature melting fluorescence assays on oligonucleotides , electrophoresis analysis of quadruplex formation (Koeppel et al, 2001), electrospray ionization mass spectrometry (Rosu et al, 2003a), and the telomeric repeat amplification protocol that measures telomerase activity in cell extracts (Gomez et al, 2002) (for review, see Guittat et al, 2004). The ligands that stabilize G-quadruplex structures include cationic porphyrins (Han et al, 1999Dixon et al, 2007), perylenes (Fedoroff et al, 2000), amidoanthracene-9,10-diones (Perry et al, 1998), 2,7-disubstituted amidofluorenones (Perry et al, 1999), acridines Harrison et al, 2003), ethidium derivatives (Koeppel et al, 2001;Rosu et al, 2003a), disubstituted triazines , fluoroquinoanthroxazines (Kim et al, 2003a), indoloquinolines (Caprio et al, 2000), dibenzophenanthrolines , bisquinacridines (Teulade-Fichou et al, 2003), pentacyclic acridinium (Gowan et al, 2001), telomestatin (Shin-ya et al, 2001), and the recently discovered bisquinolinium derivatives Pennarun et al, 2005;De Cian et al, 2007) (for review, see Kerwin, 2000;Cuesta et al, 2003;Guittat et al, 2004;Pendino et al, 2006). Because of the peculiar features of the quadruplex structure, compared with classic double-stranded B-DNA, a selective recognition of telomeric G-quadruplex by small-molecule ligands should be possible Parkinson et al, 2002;Clark et al, 2003;Ambrus et al, 2006).…”
mentioning
confidence: 99%